2019
DOI: 10.1017/sjp.2019.35
|View full text |Cite
|
Sign up to set email alerts
|

Variables Related to Victimization and Perpetration of Dating Violence in Adolescents in Residential Care Settings

Abstract: Violence in dating relationships constitutes a serious problem, thus, the study of related factors could help to better understand this violence and intervene in it. This study had three goals: (1) To analyze the prevalence of dating violence in adolescents under residential care settings according to sex and age; (2) to explore the relationships between victimization and perpetration in adolescents’ dating violence, sexist attitudes and clinical variables; and (3) to identify variables associated to adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…While most of the studies tested gender differences, n = 4 studies did not provide separate data for female and male adolescents (Cuadrado‐Gordillo et al., 2020; Dosil et al., 2019; García‐Díaz et al., 2018; Sebastián et al., 2014), n = 7 studies reported separate data for female and male adolescents but gender differences were not tested (Archer et al., 2010; Dixe et al., 2020; Esparza‐Martínez et al., 2019 5 ; Fernández‐Fuertes & Fuertes, 2010; Fernández‐Fuertes et al., 2020; Fernández‐González et al., 2013; Young et al., 2018), n = 1 study reported clusters among couples (Burk & Seiffge‐Krenke, 2015), and n = 1 study examined males only (Diaz‐Aguado & Martinez, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the studies tested gender differences, n = 4 studies did not provide separate data for female and male adolescents (Cuadrado‐Gordillo et al., 2020; Dosil et al., 2019; García‐Díaz et al., 2018; Sebastián et al., 2014), n = 7 studies reported separate data for female and male adolescents but gender differences were not tested (Archer et al., 2010; Dixe et al., 2020; Esparza‐Martínez et al., 2019 5 ; Fernández‐Fuertes & Fuertes, 2010; Fernández‐Fuertes et al., 2020; Fernández‐González et al., 2013; Young et al., 2018), n = 1 study reported clusters among couples (Burk & Seiffge‐Krenke, 2015), and n = 1 study examined males only (Diaz‐Aguado & Martinez, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Five samples, two from Germany (Beckmann et al., 2019; Kliem et al., 2018) and three from Spain (Calvete et al., 2016; Cava et al., 2015; Cava, Martínez‐Ferrer, et al., 2020), met all criteria of quality and achieved a total score of 0. Six samples, one from Germany (Blättner et al., 2015), two from Spain (Dosil et al., 2019; Fernández‐González et al., 2013), two from the United Kingdom (Stanley et al., 2018; Young et al., 2018), and one from Italy (Stanley et al., 2018) scored 4, and three further samples, one from Belgium (Glowacz et al., 2018), one from Portugal (Dixe et al., 2020), and one from Spain (Sebastián et al., 2014), scored 5. All other studies presented 1, 2, or 3 points.…”
Section: Resultsmentioning
confidence: 99%
“…Contrariamente a lo esperado de las iniciativas legislativas con perspectiva de género, pero en línea con los hallazgos sociológicos y epidemiológicos en esta población y en el contexto de noviazgo (Gracia-Leiva et al, 2019;Kennedy et al, 2021;Smith-Darden et al, 2017;Wincentak et al, 2017), los chicos tienen una mayor prevalencia de victimización que las chicas, y éstas resuelven los conflictos en el noviazgo valiéndose en mayor medida de la violencia, específicamente la psicológica y física leve con un incremento de la prevalencia en ambas manifestaciones de la violencia en torno al 50% sobre los chicos. No obstante, este resultado no es generalizable a otros estudios, habiéndose hallado una mayor prevalencia de violencia en los chicos (Rubio-Garay et al, 2019) o que no hay asociación entre el sexo y violencia (Dosil et al, 2019;Fernández-González et al, 2017;Menesini et al, 2011;Reidy et al, 2016), debiendo, por tanto, circunscribirse a esta población y contexto. En todo caso, ambos, chicos y chicas, son víctimas y victimarios (Menesini et al, 2011).…”
Section: Discussionunclassified
“…The data on the greater victimization through severe forms of abuse against women seem to be incongruent with some studies that identify this group as the greatest perpetrators of different types of abuse as compared to men [ 6 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 89%
“…In Spain, these dynamics are similar. In 2019, a published study confirmed that in a sample of young Spanish individuals, 91.5% were identified as aggressors in their relationships, and 88.6% stated that they had been victims of these aggressions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%